Identification and aroma characteristics of various tea types produced from ‘Yiluxiang’ and ‘Yelaixiang’ tea varieties - YOU Xiaomei; LI Xinlei; CHEN Zhihui; KONG Xiangrui; SHAN Ruiyang; CHEN Changsong (Xibei zhiwu xuebao)
[Objective] The study aims to examine the quality and aroma characteristics of various tea types produced from tea varieties ‘Yiluxiang’ (YILX) and ‘Yelaixiang’ (YELX) and accelerate their application. [Methods] Green tea, oolong tea, black tea, and white tea were prepared with YILX and YELX as raw materials and with ‘Huangdan’ as control. Sensory quality evaluation and aroma component of tea samples were investigated. [Results] The quality of green tea, oolong tea, black tea, and white tea produced from YILX and YELX showed varying degrees of improvement compared to ‘Huangdan’. The green tea produced by YILX was of the highest quality, characterized by floral fragrance and enriched with a high level of floral and fruity aroma components, including β-ocimene and (Z )-3-hexenyl hexanoate, among others. Oolong tea made from YELX had the best quality with distinct floral fragrance and the highest content of various floral and fruity aroma components, including β-ocimene, phenylethanol, and (Z)-3-hexenyl hexanoate. The sensory scores of the black teas made from YILX and YELX were comparable, as both exhibit floral aromas. While YELX aroma quality was mainly composed of flower, fruit, and milk aroma components such as geraniol, YILX was mainly composed of fragrant and long-lasting components such as methyl salicylate. Teas made from YELX was of the highest quality, with a milk powder fragrance and the highest content of aroma components such as geraniol, (Z )-3-hexenol and so on. [Conclusion] Both YILX and YELX were suitable for making green tea, oolong tea, black tea, and white tea. YILX is better suited for making green tea and black tea, while YELX is more suitable for making oolong tea, black tea, and white tea.